2009
DOI: 10.1108/17410381011011470
|View full text |Cite
|
Sign up to set email alerts
|

Risk calculations in the manufacturing technology selection process

Abstract: PurposeThe purpose of this paper is to present result obtained from a developed technology selection framework and provide a detailed insight into the risk calculations and their implications in manufacturing technology selection process.Design/methodology/approachThe results illustrated in the paper are the outcome of an action research study that was conducted in an aerospace company.FindingsThe paper highlights the role of risk calculations in manufacturing technology selection process by elaborating the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 26 publications
0
14
0
2
Order By: Relevance
“…This makes flexibility an increasingly important attribute of manufacturing. Manufacturing technology selection has been an area of great interest for academics and industrial managers alike because of the constant developments in the manufacturing technology and the industrial implications of these rapid developments (Farooq and O'Brien, 2010). According to Chryssolouris and Lee (1992), flexibility of a manufacturing system is determined by its sensitivity to change' while Nagarur (1992), defines flexibility as the ability of the system to quickly adjust to any change in relevant factors like product, process, loads and machine failure.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This makes flexibility an increasingly important attribute of manufacturing. Manufacturing technology selection has been an area of great interest for academics and industrial managers alike because of the constant developments in the manufacturing technology and the industrial implications of these rapid developments (Farooq and O'Brien, 2010). According to Chryssolouris and Lee (1992), flexibility of a manufacturing system is determined by its sensitivity to change' while Nagarur (1992), defines flexibility as the ability of the system to quickly adjust to any change in relevant factors like product, process, loads and machine failure.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Problems arise in this area because of the lack of local know-how, resulting in the end product being perceived to be of poor quality in the consumer market to which the technology was transferred and creating an important barrier that those involved in the process, whether on the technology source or receiver side, must overcome. This issue was also highlighted by Farooq and O'Brien (2010) who suggested that the variables in the process should be analyzed taking into account the company's objectives and strategies to avoid di±culties that could compromise the quality of the end product.…”
Section: Variables and Impacts In A Ttpmentioning
confidence: 99%
“…Collaboration may enable new equipment to be installed faster and at lower costs, and facilitates equipment optimization, troubleshooting and upgrading (Lager and Frishammar, 2010). Supplier resources that might facilitate the adoption process include instruction manuals, on-site training and temporary use of supplier operators (Farooq and O'Brien, 2010;Lager and Frishammar, 2010). Thus, the second research hypothesis was developed:…”
Section: H1mentioning
confidence: 99%